ANALISIS AGROINDUSTRI SUSU KEDELAI DI KELURAHAN PURWODADI KECAMATAN TAMPAN KOTA PEKANBARU PROVINSI RIAU (KASUS PADA USAHA SUSU KEDELAI BAPAK ANAS) - Endro; Fahrial (DINAMIKA PERTANIAN, 2022)
The purpose of this work is to analyse the characteristics of entrepreneurs and business profiles, the production process and the use of production inputs, production costs, output, sales price, income, and the efficiency and added value of business in the soy milk agroindustry. This study used a survey method in Purwodadi Village, Tampan District, Pekanbaru City, Riau Province. Data were analysed using descriptively qualitatively and quantitatively. The results showed that the characteristic features of soymilk entrepreneurs were productive age, high school education, high entrepreneurial experience and relatively small family members. The business profile shows that the soymilk agroindustry is classified as a micro-enterprise. The production process of soy milk begins with shaking and washing, grinding, boiling, filtering, heating, and packaging. The use of inputs consisted of raw materials i.e., soybeans 72 kg/month, labour 11.59 HOK/month and supporting materials namely water 1.368 l/month, sugar 120 kg/month, food flavours 600 ml/month, salt 7200 grams/month, pandan leaves 1 sheets/month, plastic wrapping 9360 sheets/month and firewood up to m3/month. The of production cost of soy milk was Rp. 5,545,864/month, which consisted of variable costs IDR 5,481.150/month and fixed costs IDR 64,714/month. Soy milk production was obtained as much as 1,080 liters/month with a selling price of IDR 6,667/liter. Gross income was IDR 7,200,000/month and net income was IDR. 1,654,136/month. The efficiency (RCR) of soy milk was 1.30 and it means soy milk was profitable and feasible. The added value obtained from the soy milk agroindustry was IDR 39,068/liter with a value-added ratio of 39.07%.